Simultaneous Release of Fe and As during the Reductive Dissolution of Pb-As Jarosite by Shewanella putrefaciens CN32 - Smeaton, C.; Walshe, G.; Smith, A.; Hudson-Edwards, K.; Dubbin, W.; Wright, Kathleen; Beale, A.; Fryer, B.; Weisener, C. (American Chemical Society, 2012)
Jarosites are produced during metallurgical processing, on oxidized sulfide deposits, and in acid mine drainage environments. Despite the environmental relevance of jarosites, few studies have examined their biogeochemical stability. This study demonstrates the simultaneous reduction of structural Fe(III) and aqueous As(V) during the dissolution of synthetic Pb–As jarosite (PbFe3(SO4,AsO4)2(OH)6) by Shewanella putrefaciens using batch experiments under anaerobic circumneutral conditions. Fe(III) reduction occurred immediately in inoculated samples while As(V) reduction was observed after 72 h. XANES spectra showed As(III) (14.7%) in the solid phase at 168 h coincident with decreased aqueous As(V). At 336 h, XANES spectra and aqueous speciation analysis demonstrated 20.2% and 3.0% of total As was present as As(III) in the solid and aqueous phase, respectively. In contrast, 12.4% of total Fe was present as aqueous Fe(II) and was below the detection limits of XANES in the solid phase. TEM-EDS analysis at 336 h showed secondary precipitates enriched in Fe and O with minor amounts of As and Pb. Based on experimental data and thermodynamic modeling, we suggest that structural Fe(III) reduction was thermodynamically driven while aqueous As(V) reduction was triggered by detoxification induced to offset the high As(V) (328 μM) concentrations released during dissolution.